Can Playfulness Be Designed? Understanding Playful Design through Agency in Astroneer (2019) - Bódi, Bettina (Eludamos: Journal for Computer Game Culture, 2021)
The cultural phenomenon that Minecraft (Mojang 2009) has become over the past decade demonstrates, amongst many other things, a powerful appetite for games where the player is thrown in a virtual playground to do as they please. Aerospace-themed survival-crafting game Astroneer (2019) by System Era Softworks is one of many such video games released since that capitalizes on this trend. The appeal of such games lies in that they can be enjoyed by players with various interests, abilities and backgrounds: the average player can mine, build, and fight whatever and whomever they please, or even create entire games within the game. The design of such games is, in many ways, less constricted than that of other avatar-based genres, such as action-adventures or first-person shooters. Freedom, playfulness, and creative play are often associated with such design, which evoke questions about agency. This article connects these notions and asks: can agency help us better understand how playfulness can be designed? By interrogating the paratexts surrounding the game’s development to see how developers discussed design decisions that facilitate playfulness, this article illustrates how thinking of agency as something afforded by game design can be a productive analytical tool to identify design decisions that facilitate player freedom and creative thinking. This, in turn, sheds light on whether, and if so how, playfulness can be designed.